Antifungal activity of non-conventional yeasts against Botrytis cinerea and non-Botrytis grape bunch rot fungi - Maluleke, Evelyn; Jolly, Neil Paul; Patterton, Hugh George; Setati, Mathabatha Evodia (Frontiers in Microbiology, 2022)
Grapes harbour a plethora of non-conventional yeast species. Over the past two decades, several of the species have been extensively characterized and their contribution to wine quality is better understood. Beyond fermentation, some of the species have been investigated for their potential as alternative biological tools to reduce grape and wine spoilage. However, such studies remain limited to a few genera. This work aimed to evaluate the antagonistic activity of grape must-derived non-conventional yeasts against Botrytis cinerea and non-botrytis bunch-rotting moulds and to further elucidate mechanisms conferring antifungal activity. A total of 31 yeast strains representing 21 species were screened on different agar media using a dual culture technique and liquid mixed cultures, respectively. Pichia kudriavzevii was the most potent with a minimum inhibitory concentration of 102 cells/mL against B. cinerea but it had a narrow activity spectrum. Twelve of the yeast strains displayed broad antagonistic activity, inhibiting three strains of B. cinerea (B05. 10, IWBT FF1 & IWBT FF2), a strain of Aspergillus niger and Alternaria alternata. Production of chitinases and glucanases in the presence of B. cinerea was a common feature in most of the antagonists. Volatile and non-volatile compounds produced by antagonistic yeast strains in the presence of B. cinerea were analysed and identified using gas and liquid chromatography mass spectrometry, respectively. The volatile compounds identified belonged mainly to higher alcohols, esters, organosulfur compounds and monoterpenes while the non-volatile compounds were cyclic peptides and diketopiperazine. To our knowledge, this is the first report to demonstrate inhibitory effect of the non-volatile compounds produced by various yeast species.